The Mysterious Ruler of Nothingness and Identity: About the Act, Will and Other Volitional Concepts and Their Significance for Systematic Philosophy - Wyszkowski, Konrad; Aftyka, Kamil (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
The purpose of the following text is to present what I have established about volitional concepts such as act or will. I claim that the concepts play the most important rôles in epistemology and ontology (theoretical philosophy), philosophy of right (“die Rechtsphilosophie,” practical philosophy), and consequently in systematic philosophizing. The main part of the text deals with act, will and other volitional concepts as the main subject of the philosophy of right to exhibit these concepts at their finest. Especially the one of will, as the pars pro toto of volitionality, is examined and exhibited. The concept of will is in its element in the philosophy of right, so the latter is the best place for its examination. Eventually, after the summary of the main part, the advertisement of an application of the concept of will to the general philosophical issues is presented. This concept, as the spirit unto itself, is introductorily confronted with epistemological and ontological problems such as the problem of novelty (of which an instance is known as the Meno’s paradox), the ontological status of laws of nature and laws of history, the problem of the emergence of intersubjectivity and the character of “true infinity” and of sublation. I wrote the text in a manner highlighting the moments of the presented reasoning that may stimulate interest and curiosity of the reader. In highlighting thus: the object, goals and theses, claims. This, necessarily, puts in the shade reasonings, viz., assumptions, premises, and inferences themselves and makes the text sound like a summary. This is not a disguise: this is truly a summary of much broader considerations.